2012
DOI: 10.1007/s10103-012-1166-4
|View full text |Cite
|
Sign up to set email alerts
|

The efficacy of the use of IR laser phototherapy associated to biphasic ceramic graft and guided bone regeneration on surgical fractures treated with wire osteosynthesis: a comparative laser fluorescence and Raman spectral study on rabbits

Abstract: The aim of the present study was to assess, by Raman spectroscopy and laser fluorescence, the repair of surgical fractures fixed with wire osteosynthesis treated or not with infrared laser (λ780 nm, 50 mW, 4 × 4 J/cm(2) =16 J/cm(2), ϕ=0.5 cm(2), CW) associated or not to the use of hydroxyapatite and guided bone regeneration. Surgical tibial fractures were created under general anesthesia on 15 rabbits that were divided into five groups, maintained on individual cages, at day/night cycle, fed with solid laborat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0
4

Year Published

2013
2013
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 33 publications
1
8
0
4
Order By: Relevance
“…Several studies have demonstrated that NIR light irradiation therapy could be used to improve bone healing and the regeneration process. NIR light therapy at 790 nm was reported to guide bone tissue regeneration on rabbits' tibial fractures with wire osteosynthesis or internal rigid fixation 122 - 124 . In addition, 850 nm NIR light phototherapy demonstrated the same ability to stimulate cell proliferation and guide bone tissue regeneration in a rodent model 125 .…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have demonstrated that NIR light irradiation therapy could be used to improve bone healing and the regeneration process. NIR light therapy at 790 nm was reported to guide bone tissue regeneration on rabbits' tibial fractures with wire osteosynthesis or internal rigid fixation 122 - 124 . In addition, 850 nm NIR light phototherapy demonstrated the same ability to stimulate cell proliferation and guide bone tissue regeneration in a rodent model 125 .…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have showed that laser therapy is able to increase bone cell proliferation and to stimulate cell osteogenic properties (21-23). LLLT creates a number of environmental conditions that accelerate the healing of bone fractures and defects.…”
Section: Discussionmentioning
confidence: 99%
“…The effects of near-infrared LPT have shown to demonstrate physiological stimulation of the fractured site. 18 This was proven to be effective as measured by Raman spectroscopy, which showed an increasing deposition of calcium hydroxyapatite, and by fluorescent reading, which showed a decrease in the organic components. 18 Studies have also shown that bone irradiated at the infrared (IR) wavelength demonstrates increased osteoblastic proliferation and activity and collagen deposition as well as a greater percentage of new bone formation when compared with bone that is not irradiated.…”
Section: Potential Roles For Optical Spectroscopiesmentioning
confidence: 97%
“…18 This was proven to be effective as measured by Raman spectroscopy, which showed an increasing deposition of calcium hydroxyapatite, and by fluorescent reading, which showed a decrease in the organic components. 18 Studies have also shown that bone irradiated at the infrared (IR) wavelength demonstrates increased osteoblastic proliferation and activity and collagen deposition as well as a greater percentage of new bone formation when compared with bone that is not irradiated. 19 Low-level laser therapy (LLLT) combined with BMPs and guided tissue regeneration has also been effective in improving bone healing.…”
Section: Potential Roles For Optical Spectroscopiesmentioning
confidence: 97%